Upaya Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa Menggunakan Model Pembelajaran Team Games Tournament Di Kelas VIII SMP Negeri 1 Sosa - Azhari Hasibuan, Sundut; Hamida Hasibuan, Nur; Canra Pulungan, Ali (Journal of Information System and Education Development, 2025)
The purpose of this study was to improve the mathematical critical thinking ability of students in class VIII-2 SMP Negeri 1 Sosa by using the Team Games Tournament type cooperative learning model. Based on the results of the mathematical critical thinking ability test given to students, the number of students who completed the initial observation was 3 people, cycle I was 16 people, and cycle II was 23 out of 26 students. While the percentage of classical completeness in the initial observation was 11.54%, cycle I was 61.54%, and cycle II was 88.46%. The increase in the percentage of classical completeness was 76.92%. In addition, for each indicator of students' mathematical critical thinking ability, the percentage of mastery of the indicator of mathematical critical thinking ability was 76.92%. In addition, for each indicator of students' mathematical critical thinking ability, the percentage of mastery of the best indicator of mathematical critical thinking ability is indicator 3, namely the skill of recognizing and solving problems, which is 85.19%, while the lowest percentage of mastery is indicator 5, namely the skill of concluding Based on the results of this study, it can be concluded that the TGT type cooperative learning model can improve the mathematical critical thinking ability of students in class VIII-2 SMPN 1 Sosa